System- und Prozeßtechnik für das simultane Löten mit Diodenlaserstrahlung von elektronischen Bauelementen - Hierl, Stefan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)
The electronic production requires a powerful and economic joining technology which copes with the trends to miniaturisation and integration. But more and more established soldering techniques border their limits e.g. when solder joints are difficult to access or when substrates or electronic devices have a low thermal resistance. The simultaneous laser soldering offers a solution for such joining tasks. Therefore the aim of the Dr.-Thesis is to provide the basics of the system and process technology for this joining method. A prototype of a laser soldering machine was developed, which mainly consists of a soldering head with four diode lasers and an adaptive beam shaping for generating variable light lines. The investigations have shown that the simultaneous laser soldering is suited to join SMDs of different shapes and sizes both on standard substrates and on 3-D MID